The Complementary Nature of Trust and Contract Enforcement - Björn Bartling; Ernst Fehr; David B. Huffmann; Nick Netzer; David B. Huffman (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Under weak contract enforcement the trading parties' trust, defined as their belief in other's trustworthiness, appears important for realizing gains from trade. In contrast, under strong contract enforcement beliefs about other's trustworthiness appear less important, suggesting that trust and contract enforcement are substitutes. Here we show, however, that trust and contract enforcement are complements. We demonstrate that under weak contract enforcement trust has no effect on gains from trade, but when we successively improve contract enforcement, larger effects of trust emerge. Likewise, improvements in contract enforcement generate no increases in gains from trade under low initial trust, but cause high increases when initial trust is high. Thus, the effect of improvements in contract enforcement is trust-dependent, and the effect of increases in trust is dependent on the strength of contract enforcement. We identify three key ingredients underlying this complementarity: (1) heterogeneity in trustworthiness; (2) strength of contract enforcement affecting the ability to elicit reciprocal behavior from trustworthy types, and screen out untrustworthy types; (3) trust beliefs determining willingness to try such strategies.
Keywords: C91; D02; D91; E02; 330; trust; contract enforcement; complementarity; equilibrium selection; causal effect; screening; belief distortions; institutions